2013
DOI: 10.1116/1.4825105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trimethylsilane pressure on hot-wire chemical vapor deposition chemistry using vacuum ultraviolet laser ionization mass spectrometry

Abstract: Detecting free radicals during the hot wire chemical vapor deposition of amorphous silicon carbide films using single-source precursors J. Vac. Sci. Technol. A 24, 542 (2006); 10.1116/1.2194023 Vacuum ultraviolet mass-analyzed threshold ionization spectroscopy of hexafluorobenzene: The Jahn-Teller effect and vibrational analysisIn this study, the authors investigated the effect of sample pressure on the reaction chemistry of trimethylsilane (TriMS) in the hot-wire chemical vapor deposition (CVD) process. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…From it, the ionization cross section ratio of He to TriMS has been determined to be 3.8 × 10 −4 using the 10.5 eV SPI. 25 Therefore, the contribution from EI is present, but minor, in the SPI mode used in this work. This explains the weakness of the observed parent MMS ion peak and its fragment ion peaks.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…From it, the ionization cross section ratio of He to TriMS has been determined to be 3.8 × 10 −4 using the 10.5 eV SPI. 25 Therefore, the contribution from EI is present, but minor, in the SPI mode used in this work. This explains the weakness of the observed parent MMS ion peak and its fragment ion peaks.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…The amount of CH 4 varied from 2.5% to 6.25% that of H 2 . Our previous work 25 has characterized the ionization cross section of CH 4 is comparable to that of H 2 [σ(H 2 )/σ(CH 4 ) = 0.88 ± 0.04] when using the SPI mode. Considering the low intensity of the H 2 peak, CH 4 will escape detection if it is produced in a lesser amount.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This constitutes part of our ongoing efforts on the gas-phase reaction chemistry assumed by various single-source organosilicon precursors in the process of hot-wire CVD. Our previous studies on trimethylsilane 12,13 and tetramethylsilane 14 have shown that free-radical chain reactions dominate in the secondary gasphase reactions with these two precursors when using W filaments. The reactive silene intermediates are also involved, but their contributions are minor.…”
Section: Introductionmentioning
confidence: 99%
“…15 It involves radical recombination reactions between methyl radicals as well as hydrogen abstraction reactions. In the experiments with 1.2 Torr of DMS for the temperatures of 1300 and 1400°C, the intensity ratio of ethene to propene was found to range from 0.30 to 1.37.…”
Section: Intensity (Au)mentioning
confidence: 99%